Ontogeneza i filogeneza sztuki: ku naturalistycznemu rozumieniu twórczości w ujęciu Ellen Dissanayake - Luty, Jerzy (Kultura-Społeczeństwo-Edukacja, 2025)
The aim of this article is to present and critically examine Ellen Dissanayake’s ethological theory of art, which frames artistic behavior as an evolutionary adaptation. The core problem addressed is the lack of a coherent, biologically grounded framework for understanding the origins and functions of art in both ontogenetic and phylogenetic contexts. Unlike traditional conceptions that define art through its symbolic content or aesthetic objects, Dissanayake proposes the concept of “artification” – a behavior she characterizes as “making special” – as a universal and innate human tendency. The methodology is interdisciplinary and theoretical, integrating findings from ethology, evolutionary anthropology, cognitive psychology, developmental pedagogy, archaeology, and neuroscience. The analysis relies on Dissanayake’s foundational works and contemporary critiques to trace the biological and developmental roots of art related behaviors. Key findings suggest that early artistic behaviors, such as rhythmic gestures, ornamentation, and mark-making, likely evolved as adaptive responses to environmental uncertainties. These behaviors originate in the mother-infant dyad and manifest through emotional bonding, repetitive patterns, and heightened sensory experiences – behaviors that later develop into ritualistic and artistic expressions within communal settings. The theory posits that proto-aesthetic behaviors promote social cohesion, emotional regulation, and cognitive development, ultimately contributing to reproductive success. In conclusion, Dissanayake’s model offers a compelling naturalistic account of art, positioning it not as a cultural artifact alone but as an evolutionary inheritance embedded in human nature. This reconceptualization challenges conventional art theory and calls for broader, behavior-based definitions of artistic phenomena.